DOI: 10.28971/212006ar109
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Tactical Knowledge and Tactical Performance for Varying Levels of Expertise

Abstract: This study examines the relationship between off-the-ball tactical knowledge and off-the-ball tactical performance of college-age female participants' (n = 34) with varying levels of expertise in territorial games. Tactical knowledge was measured using the Tactical Knowledge Instrument (TKI), which assessed participant responses when solving a "maintaining possession" tactical problem on a game board. The Game Performance Assessment Instrument (GPAI) measured participants' tactical performance while they playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These results seem to indicate that along with age, differences between experts and novices involve the defensive, off-the-ball aspects of the game. These require greater explicit attention in the training process, though often training processes and informal learning focus on the on-the-ball and offensive components (Blomqvist, et al, 2005;Auld, 2006;. These findings also lend weight to the suggestion by French, et al (1995) that since the context of the game performance and the underlying factors are changing, the criterion used to evaluate and define expertise can change with age.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…These results seem to indicate that along with age, differences between experts and novices involve the defensive, off-the-ball aspects of the game. These require greater explicit attention in the training process, though often training processes and informal learning focus on the on-the-ball and offensive components (Blomqvist, et al, 2005;Auld, 2006;. These findings also lend weight to the suggestion by French, et al (1995) that since the context of the game performance and the underlying factors are changing, the criterion used to evaluate and define expertise can change with age.…”
Section: Resultsmentioning
confidence: 68%
“…Discussion Previous research has shown that players with higher expertise are superior in cognitive components of game performance. This superiority has been confirmed both in authentic game play through observational instruments that assess decision-making and skill-execution components separately (e.g., French & Thomas, 1987;Thomas, 1989;McPherson & Nevett, et al, 2001;Auld, 2006), as well as in isolated conditions through the use of written knowledge tests, interviews, or video-based situations (e.g., French & Thomas, 1987;French, et al, 1996;Nevett & French, 1997;Garcia Lopez, et al, 2010). The present study suggests that this remains true when the interference of execution ability is minimized.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations